2021
DOI: 10.1177/03635465211031853
|View full text |Cite
|
Sign up to set email alerts
|

Association of Pitch Timing and Throwing Arm Kinetics in High School and Professional Pitchers

Abstract: Background: Understanding the relationship between the temporal phases of the baseball pitch and subsequent joint loading may improve our understanding of optimal pitching mechanics and contribute to injury prevention in baseball pitchers. Purpose: To investigate the temporal phases of the pitching motion and their associations with ball velocity and throwing arm kinetics in high school (HS) and professional (PRO) baseball pitchers. Study Design: Descriptive laboratory study. Methods: PRO (n = 317) and HS (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…This can offer insight into pitch timing, which is the time spent between peak angular velocities achieved by segments across the kinetic chain. 26 , 49 It has been reported that pitchers with decreased time in the early phases of the pitching motion (ie, foot contact to peak pelvic angular velocity) had increased shoulder joint forces. 2 , 26 , 49 In contrast, increased time spent in the late phases correlated with decreased shoulder forces.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can offer insight into pitch timing, which is the time spent between peak angular velocities achieved by segments across the kinetic chain. 26 , 49 It has been reported that pitchers with decreased time in the early phases of the pitching motion (ie, foot contact to peak pelvic angular velocity) had increased shoulder joint forces. 2 , 26 , 49 In contrast, increased time spent in the late phases correlated with decreased shoulder forces.…”
Section: Discussionmentioning
confidence: 99%
“… 26 , 49 It has been reported that pitchers with decreased time in the early phases of the pitching motion (ie, foot contact to peak pelvic angular velocity) had increased shoulder joint forces. 2 , 26 , 49 In contrast, increased time spent in the late phases correlated with decreased shoulder forces. 1 One study observed that elite-level pitchers rotated their trunks later in the pitching cycle compared with lower-skilled pitchers.…”
Section: Discussionmentioning
confidence: 99%
“…During baseball pitching, force is initially generated in the legs and transferred to the hips, spine, and trunk before the upper extremity and ultimately out to the ball (3,15,20). Research indicates that pitching with proper kinematic sequencing may increase ball velocity (3,10,12,15,20). In addition to velocity, fastballs are commonly evaluated by their spin rate (21).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to velocity, fastballs are commonly evaluated by their spin rate (21). Despite numerous studies examining the effects of lower-body pitching mechanics and ball velocity (3,10,12,15,20), there is no available information describing the relationship between lower extremity power and ball spin rate.…”
Section: Introductionmentioning
confidence: 99%
“…Key differences in patterns of segmental motion have also been established between professional and high school pitchers. 32 These include the timing of maximum pelvic rotation velocity, maximum trunk rotation, and maximum shoulder internal rotation velocity, all of which act to optimize the kinetic chain. 3 In addition, high school pitchers do not demonstrate the same shoulder and elbow joint characteristics that are found typically in professional and collegiate pitchers, such as UCL thickening and ulnohumeral joint space laxity, differences that may be chronologic, adaptive, or pathologic.…”
mentioning
confidence: 99%